Pengaruh E-Wom, Reputasi dan Webqual Terhadap Keputusan Konsumen pada Pengguna Lembaga Kursus Bahasa Inggris - Muhammad Dian Ruhamak; Afif Nur Rahmadi (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2022)
The purpose of this study is to determine the effect of E-Wom, Reputation and Webqual on Consumer Decisions on English Language Course Institution Users simultaneously and partially. This study uses a quantitative approach where the population in this study is 100 respondents with a simple random sampling method to be given a questionnaire which will later be tested including instrument validity and reliability testing, then hypothesis testing and the coefficient of determination. based on the results of testing the four hypotheses, it can be concluded that all hypotheses are accepted, where the significance value of t and f count for each variable has a value less than 0.05. and the coefficient of determination indicates that consumer satisfaction is explained by e-wom, reputation and webqual by 25.1%.